SELF-ACTUALIZATION OF THE MAIN CHARACTER IN DISNEY’S CRUELLA MOVIE - Yosua Ch. Takamuntu; Ceisy N. Wuntu; Rinny S. Rorimpandey (KOMPETENSI, 2022)
The aim of this study is to reveal how the main character Estella can show her selfactualization in Disney’s Cruella movie. This study uses a qualitative research method. This study also uses a psychological approach and uses Abraham Maslow's Hierarchy of Needs theory which is useful to explain and support this research on self-actualization that is fulfilled by the main character in the Disney’s Cruella movie. The results of this study indicate that Estella as the main character is able to fulfill all her needs from physiological needs, security needs, belongingness and love needs also her esteem needs to fulfill her self-actualization as seen from the characteristics of a self-actualizing person. It can be concluded from the results of this research that Estella or Cruella has achieved self-actualization in the Disney’s Cruella movie.